What Is an Effective Signal in Crowdfunding? Evidence from Expert Researchers and a Meta-Study - Lars Hornuf; Johannes Voshaar (CESifo GmbH, 2024)
What is an effective signal in crowd funding? We asked this question to 83 expert researchers who have published the top-notch articles in this field. They stated that, in theory, strong signals include past crowdfunding success, business experience, patent ownership, and the equity share offered. Examining 145 articles published in leading business and economics journals, we find that the empirical evidence from a meta-analysis does not accord with this perception among expert researchers. Signals that expert researchers consider to be theoretically less strong are more often statistically significant predictors of crowdfunding success and have neither larger nor smaller standardized effect sizes than strong signals. A meta-regression suggests that domain-specific signals play the most important role in crowdfunding. The findings of our literature review provide important insights for investors, platform managers, and the academic review process.
Keywords: G21; D82; 330; signaling; crowdfunding; crowdinvesting; peer-to-peer lending; crowdlending; meta-study